DYSFUNCTIONAL FAMILY (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2024)
Dysfunctional families are fertile ground for neglect, abuse, secrecy, addiction, or denial. In these family systems, children’s emotional needs go unmet because the parents’ needs take precedence.One or both parents might be suffering from a substance use disorder, personality disorder, or mood disorder. Sometimes, the adults in these families have authoritarian “my way or the highway” parenting styles or have a toxic and abusive relationship with each other.In other cases, parents are emotionally immature or unavailable—caught up in workaholism, shopaholism, gambling, overeating, adulterous affairs, or other pursuits.This article shows meaning of title.